PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN KANTOR TERPADU - Noora Fithriana; Agung Nugroho Adi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
It was a quantitative research aimed to measure how significant compensation influencing employee performance and to describe the means of compensation indicators. The research collected data of questionnaire responses from 204 apparatuses state civil were randomly chosen in Malang City Block Office and analyzed them by tests of validity, reliability, normality, heteroskedasticity, simple linear regression, and descriptive statistics by using IBM SPSS 25. The research worked to get measurement of 37.4 % compensation influencing employee performance, its rests might be influenced by the other variables. The research results approved the hypothesis meaning that compensation had significant influence to employee performance. So if the City Government of Malang would like to check their apparatuses state civil performance, they have to balance it by giving them a worthy compensation. Salary as one of the compensation indicators had means of 3.990. The score meant that the respondents got proportional monthly pay. The more worthy and fair the compensation got by the apparatuses state civil of the City Government of Malang the better their performances.